Implementation of the Gender Mainstreaming Policy in Supporting Sustainable Development in Kotamobagu City - Mokoginta, Sarida; Wawointana, Thelma; Mamonto, Fitri (Technium Social Sciences Journal, 2025)
This research aims to describe and analyze the Implementation of Gender Mainstreaming (PUG) in Supporting Sustainable Development in Kotamobagu City. This research uses a descriptive qualitative approach, with 10 predetermined informants with data collection techniques namely observation, interviews and documentation with data analysis techniques through data reduction, data presentation and verification conclusion drawing. The results showed that the implementation of gender mainstreaming in Kotamobagu City faces significant challenges in various aspects that have an impact on its not optimal implementation. From the commitment sub-focus, limited understanding of the apparatus and inadequate budget allocations cause gender responsive policies and programs to be unevenly distributed at all levels of government, so that vulnerable groups such as people with disabilities and people with economic limitations have not been optimally accommodated. In the policy sub-focus, the lack of capacity of government officials and the unequal distribution of resources, especially in remote areas, further exacerbates the gap between policies and their implementation in the field. After that, in the resource sub-focus, limited time and budget for continuous training hinder the strengthening of apparatus competencies in integrating gender perspectives into the planning and implementation of development programs. In addition, the disaggregated data management sub-focus is still constrained by inadequate information systems and weak coordination between institutions, so that existing data has not been fully utilized to design gender-based policies. Therefore, it is necessary to strengthen commitment, increase human resource capacity, effective data management systems, and cross-sector coordination to support inclusive sustainable development in Kotamobagu City.